Implementasi Model Pembelajaran Problem Based Learning (Pbl) Berbasis Assessment For Learning (Afl) Dalam Pembelajaran Matematika Ditinjau Dari Komunikasi Matematik Siswa Kelas Vii Smp Negeri 1 Ngemplak Tahun Pelajaran 2015/2016 - Puspitawati, Anisa; , Dra. Nining Setyaningsih, M.Si; , M. Noor Kholid, S.Pd., M.Pd (2015)
The purposes of this study is to determine the effect learning model Problem Based Learning-based Assessment for Learning and Problem Based Learning to mathematics achievement student, the effect of mathematical communication level (high, medium, low) to mathematics achievement student, as well as the interaction between the model of learning and communication of mathematics to mathematics achievement students. The population in this study is the seventh grade students of SMP Negeri 1 Ngemplak the school year 2015/2016. Sampling using cluster random sampling technique and elected class VIIE as the experimental class VII and class VII F as the control class. Collecting data using the method of documentation, testing, and questionnaires. The data used is the value of student competency test as the initial capability data, mathematics achievement test subject matter integers, and mathematical communication student questionnaire. Test instruments include the validity and reliability. Test the balance of the initial data using the t test. Analysis of data using two-way analysis of variance test with different cell with significance level of 5%. Previously, analysis prerequisite test that is testing method Liliefors normality and homogeneity test methods Bartlett. Based on hypothesis testing, we concluded that: (1) There are effect learning model Problem Based Learning-based Assessment for Learning and Problem Based Learning to mathematics achievement student, (2) There are effect of mathematical communication level (high, medium, low) to mathematics achievement student, (3) There is no interaction between the application of mathematical models of learning and communication to the mathematics achievement of students.